2018
DOI: 10.1002/jez.2175
|View full text |Cite
|
Sign up to set email alerts
|

Developmental plasticity in reptiles: Insights from temperature‐dependent gene expression in wall lizard embryos

Abstract: Many features of the development of reptiles are affected by temperature, but very little is known about how incubation temperature affects gene expression. Here, we provide a detailed case study of gene expression profiles in common wall lizard (Podarcis muralis) embryos developing at stressfully low (15°C) versus benign (24°C) temperature. For maximum comparability between the two temperature regimes, we selected a precise developmental stage early in embryogenesis defined by the number of somites. We used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 54 publications
0
13
1
Order By: Relevance
“…Along with DNA methylation, histone modifications have been shown to play a crucial role in early embryonic development in reptiles (Feiner et al, 2018). Kdm6b is differentially expressed between gonadal transcriptomes from embryos incubated at male and female producing temperatures in TSD species Alligator mississippiensis (Yatsu et al, 2016) and Trachemys scripta elegans (Czerwinski et al, 2016).…”
Section: Current Research On Epigenetic Mechanismsmentioning
confidence: 99%
“…Along with DNA methylation, histone modifications have been shown to play a crucial role in early embryonic development in reptiles (Feiner et al, 2018). Kdm6b is differentially expressed between gonadal transcriptomes from embryos incubated at male and female producing temperatures in TSD species Alligator mississippiensis (Yatsu et al, 2016) and Trachemys scripta elegans (Czerwinski et al, 2016).…”
Section: Current Research On Epigenetic Mechanismsmentioning
confidence: 99%
“…However, there are a growing number of exceptions. For example, one study of thermal developmental plasticity in wall lizards ( Podarcis muralis ) identified suites of genes that are up‐ or downregulated at low temperatures (Feiner et al., ). Transcripts with the most extreme changes in expression profiles were associated with transcriptional and translational regulation and chromatin remodeling, suggesting possible epigenetic mechanisms underlying acclimation of early embryos to cool temperature.…”
Section: Advancing the Study Of Thermal Developmental Plasticitymentioning
confidence: 99%
“…Given the above, it is perhaps unsurprising that there is a large and growing empirical literature testing the effects of the thermal environment during incubation on the development of a range of traits across all the major reptile taxa (Deeming, 2004;Deeming & Ferguson 1991;Noble, Stenhouse, & Schwanz, 2018b). This includes incubation duration (e.g., While et al, 2015), developmental processes (e.g., gene expression; Feiner, Rago, While, & Uller, 2018a), morphology (e.g., body size, growth rate; Andrews, Mathies, Warner, & Mathies, 2009;Du et al, 2009Du et al, , 2010Monasterio, Shoo, Salvador, Iraeta, & Díaz, 2013), behavior (e.g., antipredator behavior; Burger, 1990;, performance (e.g., sprint speed; Elphick & Shine 1998), physiology (e.g., hormones, metabolic activity, energy, and nutrient content; Crews, Coomber, Baldwin, Azad, & Gonzalez-Lima, 1996Du, Shou, & Liu, 2003;Ji & Braña 1999), cognition (Amiel & Shine 2012;Clark, Amiel, Shine, Noble, & Whiting, 2014;Dayananda & Webb 2017), and, in many species, sex (Valenzuela & Lance 2004). The phenotypic variation generated in response to the thermal environment has been shown to have fitness consequences in both the short-term (e.g., via increased post-hatching growth and survival; Andrews et al, 2009) and the long-term (e.g., future reproductive success; Warner & Shine 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…Incubating wall lizard (Podarcis muralis) eggs at sub-critical temperatures had a strong influence on gene expression associated with epigenetic processes during embryonic development, including histone methyltransferase, histone deacetylase and a chromobox protein homolog associated with chromatin remodelling/organisation. Widespread chromatin remodelling under this process can lead to the transcriptional regulation of embryonic developmental processes, such as zygote cellular differentiation (Feiner et al 2018). In addition, Metzger and Schulte (2017) identified 2130 differentially methylated regions (DMRs) that responded to changes in developmental temperature in three-spine stickleback larvae.…”
Section: Temperature Dependent Epigenetic Effects On Developmentmentioning
confidence: 99%